2020
DOI: 10.4012/dmj.2019-163
|View full text |Cite
|
Sign up to set email alerts
|

Development of image analysis using Python: Relationship between matrix ratio of composite resin and curing temperature

Abstract: The aim of this study was to establish a measurement method for filler and matrix in cured resin composite (RC) using Python programming and to investigate the correlation between matrix ratio and curing temperature rise. Eight kinds of RCs were used. Backscattered electron images were taken for each cured specimen. Matrix and filler contents were calculated using Python programming with the K-means or area segmentation method. Volume measurement methods were assessed for comparison. Heat released during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Therefore, in this experiment, we first replicated existing similarity analyses on metal samples, and then experimented with bovine teeth to see if similarity analysis was possible for inorganic materials. The results showed that for the metal sample (12% Au-Ag-Pd alloy), a match of >99% with the manufacturer's declared values was detected, consistent with previous reports 4) . For alloys other than the 12% Au-Ag-Pd alloy, a lower similarity of around 50% was detected, proving, as in previous reports, that the identification of samples using cosine similarity search is extremely effective.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, in this experiment, we first replicated existing similarity analyses on metal samples, and then experimented with bovine teeth to see if similarity analysis was possible for inorganic materials. The results showed that for the metal sample (12% Au-Ag-Pd alloy), a match of >99% with the manufacturer's declared values was detected, consistent with previous reports 4) . For alloys other than the 12% Au-Ag-Pd alloy, a lower similarity of around 50% was detected, proving, as in previous reports, that the identification of samples using cosine similarity search is extremely effective.…”
Section: Discussionsupporting
confidence: 91%
“…The WDS results were used as is, without normalization. To calculate the cosine similarity between the analysis results for the alloy ingot surface and the standard values (Table 2, 12% Au-Ag-Pd alloy), we used the program reported by Hori et al 4) and computed the mean and standard deviation. Similarly, we performed cosine similarity searches between the analysis data for the bovine teeth and their standard values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation